(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 1998)
In the philosophy of Hume the factual truths cannot be reduced to formal truths. Hume thinks it is not legitimate to speak of two different worlds; there is only one the material. As a consequence of this, the problem of induction emerges how we go from a known reality to a unknown reality? The world of pure ideal does not exist in the thought of Hume; however, the author of this article affirms that the induction it is a problem because it would suppose an implicit metaphysis interpreted by the concept of infinite.